Transcriptome survey of Patagonian southern beech Nothofagus nervosa (= N. Alpina): assembly, annotation and molecular marker discovery - Torales, Susana Leonor (2012)
Nothofagus nervosa is one of the most emblematic native tree species of Patagonian temperate forests. Here, the shotgun RNA-sequencing (RNA-Seq) of the transcriptome of N. nervosa, including de novo assembly, functional annotation, and in silico discovery of potential molecular markers to support population and associations genetic studies, are described.